BASIC REQUIREMENTS ON THE CREATION OF MULTIMEDIA TECHNOLOGIES ON THE BASIS OF WEB-RESOURCES CREATED (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article describes the basic requirements for web resources created on the basis of multimedia technologies. Pedagogical, psychological, didactic and technical requirements for web resources have been developed.